Ethnomatematika: Budaya dalam Pembelajaran Matematika - Ririn Dwi Agustin; Mika Ambarawati; Era Dewi Era Dewi Kartika (Laplace : Jurnal Pendidikan Matematika, 2019)
The application of ethnomathematics-based cultural education that is integrated into learning can be through the development of learning instruments. Learning instruments consist of syllabus, learning material, student worksheets, learning resources, learning media, and evaluation tools. This studies discusses about worksheets, lesson plans, and syllabus in which ethnomatematics and character education have been included with purpose was to explain the development of syllabus, learning material, and mathematics student worksheets based on ethnomatematics in strengthening student character education.